The Relationship between Concepts of "Splendor: xwarrah" and "Dutifulness: xwēškārīh" on the basis of Middle Persian (Pahlavi) Texts and their Social Functions in Ancient Political Thought - Esmail Sangari1; Alireza Karbasi (مجله مطالعات ایرانی, 2017)
In social and political scene of ancient Iran, many words used in Middle Persian (Pahlavi) texts, have had a pragmatic function apart from their theoretical and abstract foundations. The two words "Splendor: xwarrah" and "dutifulness: xwēškārīh" are the most important words which have close relationship and have the same functions. Middle Persian texts emphasizing on Dinkard show that these two words are in direct proportion to one another. It means that dutifulness in every one is a capacity of divine light and absolute brightness which is the same as divine splendor. This divine splendor is granted to every creature depending on the level of his might and performing his creation dutifulness. This glory is the result of the best performance of dutifulness by the person who has benefited the best functions for fortifying life factors. This capacity is made in every person by performing the best kind of dutifulness in order to be similar to supernal creatures. Therefore, he will be worthy of the title "splendid: xwarrah-omand" and stands in "Farhangiān" position. In this study, through examining primary Pahlavid sources and conforming them to social structure in ancient Iran, it is aimed to show the link between these two concepts as a combination of theory and practice in ancient Iranian sages' point of view, so that they could gain the most efficiency and concrete results from people's activity in order to obtain stable might